Dual-setting brushite–silica gel cements. (1st January 2015) - Geffers, Martha; Barralet, Jake E.; Groll, Jürgen; Gbureck, Uwe
Graphical abstract: Abstract: The current study describes a dual-mechanism-setting cement that combines a brushite-forming cement paste with a second inorganic silica-based precursor. Materials were obtained by pre-hydrolyzing tetraethyl orthosilicate (TEOS) under acidic conditions following the addition of a calcium phosphate cement (CPC) powder mixed of β-tricalcium phosphate and monocalcium phosphate. Cement setting occurred by a dissolution–precipitation process, while changes in pH during setting simultaneously initiated the condensation reaction of the hydrolyzed TEOS. This resulted in an interpenetrating phase composite material in which the macropores of the CPC were infiltrated by the microporous silica gel, leading to a higher density and a compressive strength ∼5–10 times higher than the CPC reference. This also altered the release of vancomycin as a model drug, whereby in contrast to the quantitative release from the CPC reference, 25% of the immobilized drug remained in the composite matrix. By varying the TEOS content in the composite, the cement phase composition could be controlled to form either brushite, anhydrous monetite or a biphasic mixture of both. The composites with the highest silicate content showed a cell proliferation similar to a hydroxyapatite reference with a significantly higher activity per cell. Surprisingly, the biological response did not seem to be attributed to the released silicate ions, but to the release of phosphate and the adsorption of magnesium ions from the cell culture medium.